Germinação de Carthamus tinctorius L. sob restrição hídrica e estresse térmico - AMURIM, Ana Isabel Lima da Costa (2022)
Safflower is an Asteraceae with high commercial value, tolerant to adverse conditions, such as low water availability and high temperatures. It is a small oilseed crop and its cycle varies from 110 to 150 days, but in semi-arid conditions, low rainfall and high temperatures, safflower reduces its production cycle. Recently, the crop was indicated for cultivation in regions of Brazil with a semi-arid climate. It has high commercial value due to the application of oil and dye taken from its flowers in the industry, its seeds have a high content of oil rich in oleic and linoleic fatty acids. Seed productivity varies according to cultivar and growing conditions, as well as physiological and morphological parameters, which are of high importance for understanding the behavior of different cultivars under different environmental conditions. Among the characteristics of a semi-arid environment that are limiting for many crops are: temperature and water restriction. Thus, it is important to analyze the development of different cultivars subjected to different temperatures and water concentrations at the time of seedling production, so that the lowest concentration of water to be used and better development can be identified, aiming at enhancing the efficiency of the seedlings. use of water in field cultivation. Physiological analyzes indicated that photosynthesis was more expressive with water restriction of 75%; conductance was higher with 50% water restriction and transpiration was higher with 75% water restriction.Morphological analysis indicated that the cultivar with the highest number of leaves was at 946 at 25º C with 75% water irrigation. Cultivar 1470 showed the highest GVI at 38 ºC with 50% irrigation. The IMAMT 946 cultivar in the 75% treatment showed better performance in shoot size. Even under water restriction and heat stress, safflower shows good physiological development during the germination process and seedling formation. Regarding germination and morphological parameters, it is tolerant to intermediate concentrations of water and at a minimum concentration of 25% of water supply. The species is resistant to the aforementioned abiotic stresses and shows signs of a good development in semi-arid conditions, with economy of water resources in the field.